The Importance of National Cyber Security Strategy of the Republic of Macedonia - Rechkoski, Risto (International Journal of Publication and Social Studies, 2020)
Significance of the Cyber security in every society and every state in this time, at the beginning of third decade of XXI century is more than essential. Every society that has public aware of this should persist different measures and instrument in order to supply its citizens, legal entities, and also public and local institutions of authorities with possibility of secure cyber space. Strengthening the national capacities for cyber threat management and improving the cyber security have become a priority for the Republic of Macedonia. Government of Republic of Macedonia passes the National Cyber Security Strategy 2018-2022, in July 2018. The aim of the paper is to examine and pointed out the most important provisions of the Strategy. The National Cyber Security Strategy of the Republic of Macedonia is a strategic document that fosters the development of safe, secure, reliable and resilient digital environment, supported by high-quality capacities, based on cooperation and trust in the field of cyber security. This document has several parts, which are related to: Cyber trends, Challenges and threats, Cyber security principles, different Stakeholders that are involved in the Strategy, Vision and mission of the Strategy, Goals of the National Cyber Security Strategy, and its Implementation.